2021
DOI: 10.1080/00071005.2021.1926915
|View full text |Cite
|
Sign up to set email alerts
|

Policy Transfer and Isomorphism: A Case Study of the England-China Maths Teacher Exchange

Abstract: Global policy transfer has become increasingly popular in recent years, and one recent example of such policy transfer is the England-China Teacher Exchange, which was initiated in 2014 with the explicit aim of raising attainment in maths in English primary schools by trialling concepts used in Shanghai schools, Shanghai rising to the top of the PISA rankings in 2009. However, as this paper will argue this is an overly simplistic attempt to transfer a policy between two wholly different contexts, the lack of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Notably, the majority of studies focus on the national level of culture. Some examples include studies about China (Probert, 2021; Zhang and Marsh, 2016), Romania (Common and Gheorghe, 2019), or the United Kingdom (Common, 2004). Depending on what is studied, the levels and dimensions of culture are justified and applied.…”
Section: Culture and Policy Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the majority of studies focus on the national level of culture. Some examples include studies about China (Probert, 2021; Zhang and Marsh, 2016), Romania (Common and Gheorghe, 2019), or the United Kingdom (Common, 2004). Depending on what is studied, the levels and dimensions of culture are justified and applied.…”
Section: Culture and Policy Transfermentioning
confidence: 99%
“…Apart from Hofstede’s national dimensions of cultures, other national cultural aspects are also investigated. Probert (2021) studies the exam-orientated culture in education policy transfer in China. Koh (2011) emphasizes the importance of Singapore’s culture of education policymaking in its global assemblage.…”
Section: Culture and Policy Transfermentioning
confidence: 99%
“…Within the study of isomorphic pressure, there has also been pushback in the adoption of foreign models into local contexts. In a study on the England-China Maths Teacher Exchange, Probert (2022) found that 'local contexts must be taken into account for a transnational policy transfer to be successful' (p.317), suggesting that the effectiveness of these programs hinges on their embeddedness. In line with research exploring the isomorphic pressure of rankings in various parts of the world (e.g., Hazelkorn 2007;Sadlak and Liu 2007;Erkkilä and Piironen 2014;Lo 2014;Yudkevich et al 2015), Anafinova (2020) finds that national universities in Kazakhstan are pushed toward 'the visionary model of Anglo-American research university ' (p.11).…”
Section: Institutional Approachesmentioning
confidence: 99%